2023
DOI: 10.1111/mec.17125
|View full text |Cite
|
Sign up to set email alerts
|

Whole genome analyses reveal weak signatures of population structure and environmentally associated local adaptation in an important North American pollinator, the bumble bee Bombus vosnesenskii

Sam D. Heraghty,
Jason M. Jackson,
Jeffrey D. Lozier

Abstract: Studies of species that experience environmental heterogeneity across their distributions have become an important tool for understanding mechanisms of adaptation and predicting responses to climate change. We examine population structure, demographic history and environmentally associated genomic variation in Bombus vosnesenskii, a common bumble bee in the western USA, using whole genome resequencing of populations distributed across a broad range of latitudes and elevations. We find that B. vosnesenskii exhi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 140 publications
1
1
0
Order By: Relevance
“…This could reflect a greater degree of habitat fragmentation, whereby subpopulations of this species have become geographically isolated at high elevation mountain peaks. By contrast, the common North American bumblebee B. vosnesenskii shows low population structure and no evidence of decline (Heraghty et al., 2023), similar to our observations in B. pascuorum .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This could reflect a greater degree of habitat fragmentation, whereby subpopulations of this species have become geographically isolated at high elevation mountain peaks. By contrast, the common North American bumblebee B. vosnesenskii shows low population structure and no evidence of decline (Heraghty et al., 2023), similar to our observations in B. pascuorum .…”
Section: Discussionsupporting
confidence: 90%
“…In general, studies in both Europe and North America have found that relatively abundant bumblebee species such as B. terrestris do not exhibit population structure over thousands of kilometres (Colgan et al., 2022; Ghisbain et al., 2020; Heraghty et al., 2023; Lozier et al., 2011), whereas very rare and declining species (e.g. B. muscorum ) may show structure on a scale of only 10 km (Darvill et al., 2006).…”
Section: Discussionmentioning
confidence: 99%